2016
DOI: 10.3892/etm.2016.3034
|View full text |Cite
|
Sign up to set email alerts
|

Gypenoside attenuates renal ischemia/reperfusion injury in mice by inhibition of ERK signaling

Abstract: Abstract. Gynostemma pentaphyllum is a traditional Chinese medicine reported to possess a wide range of health benefits. As the major component of G. pentaphyllum, gypenoside (GP) displays various anti-inflammatory and anti-oxidant properties. However, it is unclear whether GP can protect against ischemia/reperfusion (I/R)-induced renal injury, and the underlying molecular mechanisms associated with this process remain unknown. In the present study, a renal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…An earlier study demonstrated that Gyp treatment protected rat cortical cells from glutamate-induced apoptosis by increasing the level of anti-apoptotic Bcl-2 and inhibiting pro-apoptotic Bax (Shang et al, 2006). Recent studies showed that Gyp suppressed apoptosis in cardiomycocytes in a myocardial ischemia-reperfusion injury rat model (Yu et al, 2016c) and inhibited renal cell apoptosis in a renal ischemia-reperfusion injury mouse model (Ye et al, 2016), both through upregulation of Bcl-2 and dowregulation of Bax. Gyp treatment also inhibited hepatic cell apoptosis in a mouse hepatic ischemia-reperfusion injury model by increasing Bcl-2 expression and decreasing protein levels of Bax and cytochrome c, and the activities of Caspase 3/8 (Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study demonstrated that Gyp treatment protected rat cortical cells from glutamate-induced apoptosis by increasing the level of anti-apoptotic Bcl-2 and inhibiting pro-apoptotic Bax (Shang et al, 2006). Recent studies showed that Gyp suppressed apoptosis in cardiomycocytes in a myocardial ischemia-reperfusion injury rat model (Yu et al, 2016c) and inhibited renal cell apoptosis in a renal ischemia-reperfusion injury mouse model (Ye et al, 2016), both through upregulation of Bcl-2 and dowregulation of Bax. Gyp treatment also inhibited hepatic cell apoptosis in a mouse hepatic ischemia-reperfusion injury model by increasing Bcl-2 expression and decreasing protein levels of Bax and cytochrome c, and the activities of Caspase 3/8 (Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (2016a) reported that Gyp treatment suppressed NF-kB activation by inhibition of MAPK pathway in both oxygen-glucose deprivation-reoxygenation H9c2 cell model and ischemia-reperfusion injury rat model (Yu et al, 2016a). Gyp exposure has also been shown to result in decreased production of pro-inflammatory cytokines in a renal ischemia/reperfusion injury mouse model and in β amyloidincubated N9 microglia cells (Cai et al, 2016;Ye et al, 2016). Interestingly, a recent study demonstrated that Gyp treatment attenuated inflammation in the retina and optic nerve in a mouse model of experimental autoimmune optic neuritis (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Geniposide also has been revealed to have anti-inflammatory activities by blocking the downregulation of toll-like receptor 4 (TLR4) expression that is upregulated by lipopolysaccharide (LPS) [ 18 ]. The pharmacological effects of geniposide also exhibited inhibition of histamine when released on atopic dermatitis and protective effects against ischemia and reperfusion-induced renal injury [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gypenosides are the main chemical and pharmacological substances of the Chinese herb gynostemma. Previous clinical trials have revealed that gypenosides can significantly attenuate the levels of BUN and CRE and reduces oxidative stress [ 8 ]. Chitosan, a new type of biomedical raw material, has attracted much attention in China and abroad.…”
Section: Introductionmentioning
confidence: 99%